Motivation, barriers, and willingness to participate in clinical trials for novel cancer treatments among the Vietnamese population - Pol Van Nguyen; Thanh Thi Thuy Tran; Hieu Thi Thanh Nguyen; Hien Thi Bich Tran; Van Nguyen Thanh Phan; Tram Nguyen Nguyet Luu; Bon Huu Huynh; Khoa Dang Nguyen; Trung Quang Vo (PLoS ONE, 2025)
Background Novel therapeutic approaches are actively explored and evaluated, but applying these innovations to practice depends critically on the recruitment of volunteers for clinical trials. This study aimed to assess the motivations, barriers, and willingness of the general population in Vietnam to participate in clinical trials for novel cancer treatments. Methods This analytical cross-sectional research involved the distribution of self-administered online and printed questionnaires to residents across central and southern Vietnam in December 2024. A structured 23-item questionnaire was developed based on a literature review of studies from the UK, US, and Germany. Items were culturally adapted for Vietnam and translated using a WHO-adapted four-step process, including forward translation, expert panel review, cognitive interviews with 25 participants, and final revision. Face and content validity were assessed during this process. Logistic regression analysis was conducted to determine the factors associated with the respondents’ willingness to participate in the aforementioned clinical trials. Results The questionnaires were completed by 851 participants, with the majority aged 40–50 years (30.3%). The respondents also indicated a preference for treatments with prior clinical use and coverage by health insurance (65.6%). The primary motivation for participation was intensive monitoring of conditions (83.7%). The most frequently cited barrier were concerns regarding the high risk associated with less-tested treatments (74.1%). A total of 33.6% expressed a willingness to participate in clinical trials, but fewer (18.9%) were willing to allow such involvement for their children or other family members. Finally, Kinh ethnicity, good health, and positive attitudes toward novel cancer treatments were significantly associated with an increased willingness to participate in clinical trials (p < 0.05). Conclusion This study provides critical insights into the motivation of and barriers to participation in clinical trials for novel cancer treatments. Addressing barriers and promoting motivations can contribute to supporting cancer clinical trial conductions and then improving cancer treatment effectiveness in Vietnam.